The challenges of academic history in the digital age - Briseño Senosiain, Lillian (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In this work, some of the challenges are noted, that the digital age has imposed on the task of the historiographer, and the obstacles faced by students and future historians, considered to be «digital natives», in order to develop themselves professionally. A revision was made of the sources related to the topic, in which were found the problems faced by education and the practice of history in the digital age. It is noted that students have needed to enter the digital world autodidactically and that academia has not proposed theoretical-methodological changes for its teaching and practice. Some of the obstacles that young people must face are the management of enormous quantities of data, with the capacity to analyze and store it; new sources, writings, and expressions; the hyper-textuality and the depth of the research; creativity and resources for dissemination; crowdsourcing and the manipulation of information, and the work field, epistemological changes, and the theoretical-methodological debate.